Granulomatous disease in common variable immunodeficiency: effect on immunoglobulin replacement therapy and response to steroids and splenectomy. Issue 5 (May 1996) - Spickett, G P; Zhang, J G; Green, T; Shrimankar, J
Abstract : A 40 year old white woman with common variable immunodeficiency of four years duration presented with rapidly increasing splenomegaly. Despite high dose, weekly intravenous immunoglobulin, it was impossible to raise the trough serum IgG concentration to within the normal range. While waiting for a diagnostic splenectomy, low dose corticosteroids were started, leading to a decrease in the size of the spleen and an increase in the trough IgG concentration. Both spleen and liver showed non-caseating granulomas. Following splenectomy, the corticosteroids were tailed off and the trough IgG was maintained well into the normal range on a reduced, fortnightly dose of intravenous immunoglobulin and a low dose of oral corticosteroid.